ICHTHYO-FAUNAL DIVERSITY OF RIVER KOSI IN KUMAON REGION, UTTARAKHAND - HALDAR, R. S.; PANDEY, N. N.; BISHT, H. C. S. (Journal of the Inland Fisheries Society of India, 2021)
Investigation on status of piscine diversity and species composition in river Kosi was conducted during 2010-2011. The Kosi river is situated in the south-west area of the Kumaon region in Uttarakhand State. The whole study area of River Kosi from Berchuakot (originating point of river Kosi) to Ramnagar (Foothill) was divided in 3 zones and selected six sampling spots. The average annual CPUE calculated was highest along downstream followed by mid stream zone. The fish fauna is comprised of Mahseers, Snow trouts, minor carps, sucker heads, loaches, cat fishes and Baam. Total 26 fish species belongings to 6 families were recorded during the study period. Mahseer is the major fishery in this river system, which gravimetrically contributes 31.0 - 57.0% followed by snow trout. Key words: River Kosi, CPUE, Mahseer, Snow trout, ranching